Universitas Milik Perusahaan sebagai Strategi Talent Pooling: Peluang atau Tantangan? - Rocky (Fakultas Psikologi Universitas Pancasila, 2021)
Some companies in Indonesia established university as their business units. Apart from educating the young generation, these company-owned universities were also meant to attract talent into the company. Hence, senior employees were often tasked to share the classified practices of the company. However, this strategy could backfire if graduates joined the competitors instead. This research set out to uncover whether company owned university is a good strategy for attracting prospective talents. The construct used in this study is organizational attraction; the positive attitude of an individual to an organization. Quantitative method were used to collect the data. 474 students (178 males, 296 females) participated in this research and were divided into two groups; those who study in company owned university and those who do not. Independent-sample t-test was used to compare the organization attraction of the two groups. Result showed significant difference between company owned university students (M= 54.07. SD= 7.937) and private university (M= 51.69. SD= 7.716); t(472)= 3.309; p= 0.001. This result indicates that the students who study at company owned university were more attracted to work at holding company rather than student who studying at private university.